MEDIATING ROLE OF JOB SATISFACTION IN RELATIONSHIP BETWEEN RETENTION, COMMITMENT, COMPETENCE IN IMPROVING PERFORMANCE - Santika, Reva Ragam; Liswandi, Liswandi; Hidayah, Zainur (UNIVERSITAS PAKUAN, 2021)
This Study aims to investigate the effect of retention, commitment competence on lecturer performance through job satisfaction as moderating variable. Furthermore, The design of this research was survey research with a web-based cross-sectional data type. The research focuses on lecturers at one of the private university in Jakarta and the 136 sample was taken using the purposive sampling method. Data processing and hypothesis testing using the Multivariate Structural Equation Model (SEM) technique. The Research indicates that retention and competence have a positive but not significant influence on job satisfaction, while commitment has a significant positive influence on job satisfaction and competence has a significant positive influence on performance. In particular, the moderating influence of job satisfaction does not have a significant influence on the relationship between retention, commitment, and competence on lecturer performance The Conclusion of this study that retention, competence have positive effect but not significant on job satisfaction, competence has positive significant on Lecturer Performance and lecturer commitment has positive significant on job satisfaction but doesnt have significant effect to Lecturer performance